2017
DOI: 10.1097/qai.0000000000001252
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility and HIV Prevalence Among Female Market Traders in East Africa in 2014

Abstract: Background The contribution of women’s mobility to the HIV/AIDS epidemic in Africa is poorly understood, despite women’s high mobility and evidence that it is associated with higher-risk sexual behavior. We sought to measure levels of mobility, HIV prevalence, and related risk behaviors among female traders in Kisumu, Kenya. Methods We used GPS mapping to develop a probability-based sample and recruited 305 female market traders for participation in a survey and voluntary HIV counseling and testing in 2014. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…widowhood) may increase HIV risk at the community of origin, and social contexts at destinations and transit points facilitate multiple and higher risk sexual partnerships. We found higher HIV prevalence among female market traders (25.6% in 2013) relative to a comparable population of women of reproductive age from a household survey in Kisumu in western Kenya (15.3% in 2013) . Our qualitative research has revealed that the more mobile market traders (in contrast to those who did not travel) often supplemented their low and sporadic earnings from market trading with transactional sex; the practice was common enough that the phrase “she mixes her business” was used, we were told, to describe this practice.…”
Section: Discussionmentioning
confidence: 74%
“…widowhood) may increase HIV risk at the community of origin, and social contexts at destinations and transit points facilitate multiple and higher risk sexual partnerships. We found higher HIV prevalence among female market traders (25.6% in 2013) relative to a comparable population of women of reproductive age from a household survey in Kisumu in western Kenya (15.3% in 2013) . Our qualitative research has revealed that the more mobile market traders (in contrast to those who did not travel) often supplemented their low and sporadic earnings from market trading with transactional sex; the practice was common enough that the phrase “she mixes her business” was used, we were told, to describe this practice.…”
Section: Discussionmentioning
confidence: 74%
“…Cross‐border areas are important mixing grounds between resident populations and non‐resident populations travelling through the site or visiting the site for work, commerce or socializing. Such mixing between population subgroups provides important opportunities for HIV transmission . Accordingly, “knowing the epidemic” in a cross‐border area involves measuring viral suppression among all people who can be found in the site, and the prevention of HIV transmission must include HIV care and treatment for both resident and non‐resident groups.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study among female market vendors in Kenya found that 11.5% had migrated, changed residence, over county or national boundary in the past year and 39.3% in the past five years. Over one-third 38.3% spent nights away from their main residence in the past month, with 11.4% spending more than a week away 13 . At the time of the study, there were virtually no data available on HCT practices of people working in the market sub-sector, including market vendors and other people engaged in other market-related activities in Uganda.…”
Section: Introductionmentioning
confidence: 99%